Pemanfaatan Limbah Kayu Menjadi Produk Mainan Edukatif Bagi Anak-Anak Di Kota Palembang - M.Faiz Ghozi faiz; Husni Mubarat; Aji Windu Viatra (VisArt: Jurnal Seni Rupa dan Design, 2024)
Wood waste is wood residue or parts of wood that are considered no longer of economic value, usually the remaining pieces of wood consist of several pieces, 25% -30% of the volume of wood material. The main problem is that wood waste has an impact on the environment and human life, such as the accumulation of wood waste which is often left to rot, piled up, or even burned. Then environmental pollution occurs, usually wood that is no longer used by the furniture industry often ends up as waste that pollutes the surrounding environment. The design method used is the Design Thinking design method with a 5W+1H data analysis approach. Therefore, it is hoped that the problem solving plan in designing wood waste can be utilized into educational toy products that are beneficial for children in the city of Palembang.